FAKTOR PENGETAHUAN, PENGALAMAN DAN KETERAMPILAN DALAM PENEMPATAN PEGAWAI KANTOR CAMAT BOYAN TANJUNG KABUPATEN KAPUAS HULU - E.01107041, Hakimin (PublikA, Jurnal Ilmu Administrasi Negara, 2012)
AbstractNeeds of employees in government institutions is based on a minimum of formal educationin high school, but it also can be based on alternative education through courses such aseducation, training, and others. Placement agency needs against employees based on skillfactors can be grouped into 3 Keywords: General knowledge, work experience, special skills, Employee Placement .